Scale-up and impact of digital and molecular diagnostic technologies on TB diagnosis and timely linkage to care in Tajikistan - Shodmon Khushvakhtov; Hayk Davtyan; Sevak Alaverdyan; Anthony D Harries; Olim Kabirov; Shahnoza Azamova; Firuza Sharipova; Safarkhon Sattorov; Asliddin Rajabov (Journal of Infection in Developing Countries)
Introduction: Tajikistan is scaling up molecular diagnostic and digital technologies to strengthen its fight against drug-resistant TB (DR-TB). The study aimed to document national scale-up GeneXpert/GxAlert and Open MRS from 2012-2019 and compare time taken from TB diagnosis to treatment and quality of data recording before and after the introduction of GxAlert.